Mathematical modelling studies of human locomotion - Hershler, Cecil (Department of Physics, 2016)
This thesis was almost wholly conducted in the confines of the Department of Bio-engineering and Medical Physics, University of Cape Town and the Bio-engineering Unit, Princess Alice Orthopaedic Hospital, Cape Town. It is an interdisciplinary thesis in that an effort has been made to bridge and thus unify the different scientific disciplines of Physics, Biology, Electrical Engineering and Mathematics. Thus the author hopes the work would appeal to as wide an audience as possible. The thesis is directed generally towards a deeper understanding of normal and pathological biped locomotion. It involves theoretical considerations in respect of model building, model testing and practical work concerned with the collection of pertinent data.